The Responsibility of Parents in Electronic Contracts Made by Minors - Dewi Astutty Mochtar; Dewi Ayu Rahayu (Faculty of Law, University of Merdeka Malang, 2024)
The quick progression of innovation and the expanding utilization of electronic stages have driven a rise in minors' interest in online exchanges. This marvel poses legitimate challenges, particularly concerning the legitimacy of electronic contracts made by minors and the degree of parental obligation. This paper looks at the legitimate system overseeing electronic contracts, including those of minors, and centres on the risk of guardians in such exchanges. Employing a regulating legitimate investigative strategy and a statute approach, the consider analyzes pertinent laws, counting gracious law and electronic exchange controls, to decide the legitimate standing of contracts made by minors. The paper also investigates the part of guardians in administering their children's computerized exercises and their legitimate commitments when their children enter into official electronic understandings. The discoveries demonstrate that whereas minors, for the most part, need the lawful capacity to enter into contracts, parents' lawful obligations change depending on each case's particular circumstances. This paper emphasizes the need for clearer, legitimate arrangements and more grounded parental supervision to ensure that minors are within the advanced age range.